Mapping Fetal Brain Development of 10 Weeks’ Gestational Age with 9.4T Postmortem MRI and Histologic Sections - Zhang, Zhonghe; Gao, Yue; Lin, Xiangtao; He, Xue; Wang, Ximing; Liu, Shuwei (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: The 10th week of gestational age (GA) is a critical period for evaluating brain development, but there is limited knowledge regarding the specific characteristics at this GA. This study is to map the brain structures at 10 weeks’ GA by using 9.4T MRI and histologic sections.MATERIALS AND METHODS: Six fetal specimens with normal brain development were imaged by using 9.4T MRI, followed by sectioning and staining. The 3D reconstruction models and quantitative measurements were obtained with Amira software.RESULTS: Four zones of the laminar organization were identified in T2-weighted MRIs, while 6 zones were delineated in the corresponding histologic sections, demonstrating a strong consistency between the two. The key structures, including the midline structures, choroid plexus, subcortical nuclei, ventricles, brainstem, and cerebellum, were clearly distinguishable with unique characteristics in both MRIs and histologic sections. The 3D visualization model effectively demonstrated the shape, spatial positions, and interrelationships of the early fetal brain structures, and their qualitative measurements were obtained. The lateral ventricles and choroid plexus constituted a substantial proportion, with the lateral ventricles accounting for 43.0% of the cerebral hemisphere and the choroid plexus comprising 41.2% of the lateral ventricles.CONCLUSIONS: At 10 weeks’ GA, the fetal brain is in an early developmental stage. The integration of 9.4T T2-weighted MRIs, 3D reconstruction, and histologic sections offers a comprehensive view of the early fetal brain’s characteristics, providing valuable insights for clinicians and anatomists.GAgestational ageUSultrasoundmicro-CTmicrofocus CT